Stress proteins are proinflammatory in vivo. - Kumar, R.
Fibrosis of biosensors, placed in vivo, represents a major hurdle to the wide-spread application of real-time monitoring of biochemical and metabolic processes in animals and humans. The fibrotic reaction is the end result of the acute inflammatory response caused by significant tissue trauma at the time of biosensor placement. This response may be associated with increased expression and release from cells of cellular stress proteins. We tested the hypothesis that subcutaneous injection of stress proteins will cause acute inflammatory swelling in an in-vivo murine model. Comparisons between groups were performed using the Dunnet T3 multiple comparison test and significance was accepted when p < 0.05. Subcutaneous injection of stress proteins (HSP70 or GRP78) was associated with significantly increased acute swelling in comparison to injections of saline or autologous serum (AS). The histological analysis demonstrated increased inflammatory cell infiltrate in the tissues that received the stress protein injections. Stress proteins, within the acute wound environment, are proinflammatory and may set the stage for peribiosensor fibrosis and eventual failure. Stress proteins may be future targets for therapeutic manipulation wherever acute inflammation is followed by problematic fibrosis.
Keywords: Dunnet T3 multiple comparison test; Acute inflammatory response; Acute inflammatory swelling; Autologous serum; Biochemical processes; Biosensor fibrosis; Cellular stress proteins; Histological analysis; In vivo proinflammatory stress proteins; In-vivo murine model; Increased inflammatory cell infiltrate; Metabolic processes; Saline; Therapeutic manipulation; Tissue trauma; Wound